2018
DOI: 10.1080/10903127.2018.1471559
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Infant Chest Compression Assist Device Using a Palm Rather Than Fingers: A Randomized Crossover Trial

Abstract: Compression with palm pressers resulted in greater compression depth without increasing hands-off time and reduced rescuer fatigue compared with compression with the TFT in simulated infant CPR with manikins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…The current ScopRev identified 29 randomized crossover manikin studies, 1 observational study, and 1 randomized study comparing various finger/hand positions. 311–340…”
Section: Neonatal Life Supportmentioning
confidence: 99%
“…The current ScopRev identified 29 randomized crossover manikin studies, 1 observational study, and 1 randomized study comparing various finger/hand positions. 311–340…”
Section: Neonatal Life Supportmentioning
confidence: 99%
“…This scoping review confirmed that two-thumb-techniques resulted in improved CC depth, lower fatigue and higher proportion of correct hand placement compared with two-finger technique 36 39–41 45. Furthermore, several alternative finger and/or hand position techniques during CC have been examined 42–51 53–57 60 88. These newer CC techniques resulted in similar performance measures when compared with the two-thumb-technique.…”
Section: Discussionmentioning
confidence: 61%
“…Adding a device that assists compressions using a palm (palm presser) compared with the two-finger technique resulted in greater (1) compression depth (41.5±1.6 vs 36.8 ±5.5 mm, p<0.001), (2) proportion of time achieving sufficiently deep CC (80.9±27.8% vs 42.4±35.4%, p<0.001) and (3) more correct hand positioning (99.9±0.5% vs . 83.9±25.3%, p=0.013) 53. However, data were sufficiently skewed as to raise doubt about whether optimal descriptive statistics were reported.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Es wurden 3 systematische Reviews [ 604 606 ], 4 Beobachtungsstudien [ 607 610 ] und 24 (randomisierte) Simulationsstudien (Anhang RR 21.2) gefunden [ 598 , 602 , 611 630 ].…”
Section: Evidenzen Für Die Leitlinienunclassified